Pengaruh Profitsbilitas, Solvabilitas, Ukuran Perusahaan Dan Ukuran KAP Terhadap Audit Delay Pada Perusahaan Jasa Yang Terdaftar Di Bursa Efek Indonesia (Studi Empiris Pada Perusahaan Sektor Property Sub Sektor Property dan Real Estate Tahun 2015-2019) - Febri Denny Irawan; Leriza Desitama Anggraini; Reny Aziatul Pebriani (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effect of profitability, solvency, firm size, and KAP size on audit delay in property and real estate sub-sector companies listed on the Indonesia Stock Exchange. The population in this study was all property and real estate companies listed on the IDX in 2015-2019. Then sampling using the purposive sampling method and obtained 14 companies. The data was secondary data in the form of annual financial statements of companies listed on the IDX during the 2015-2019 period. This study utilized multiple regression analysis. The results show that partially the profitability variable has an effect on audit delay, while the solvency variable, firm size, and KAP size have no effect on audit delay. Simultaneously, the variables of profitability, solvency, firm size, and KAP size affect audit delay. This research is expected to be useful for the property and real estate sectors.